IMPROVING STUDENT’ ABILITY IN WRITING DESCRIPTIVE TEXT THROUGH PICTURE SERIES-AIDED LEARNING STRATEGY - Lukman Hakim (MEDIA DIDAKTIKA, 2022)
This Classroom Action Research is to improve the students’ ability to write a descriptive text through the use of picture series-aided learning strategy. A class of the seventh grade students of SMP Muhammadiyah 27 Paciran Lamongan were used as the subject of the study. The required data were collected through the use of a questionnaire, an observation checklist, and a scoring rubric. The datanfrom the questionnaire indicated that the majority of students had a positive attitude toward the use of picture-series to learn descriptive text writing. Moreover, it is found from the observation data that the students participated actively in the learning process. Finally, the study also proved that the strategy improved the students’ writings with an average score increasing from 56.86 (0-100 scale) prior to the teaching learning process to 77.87 at the end treatment.